Hindu Women’s Right to Property in Bangladesh: A Grave Denial of Gender Justice - Khatun, Rafea; Ahmed, Shakil (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
With the orthodox Hindu legal system in Bangladesh, there have been substantial pessimistic arguments around Hindu women’s property rights. Due to the dominance of patriarchy within the community, intra-religious subordinate complexity, and age-old customary practices, Hindu women have been deprived of their intended advantages, which has resulted in a blatant disregard for the rights guaranteed by the sacred provision of the constitution of Bangladesh and the international human rights norms, particularly concerning the twin ideals of equality and non-discrimination. The outcome also significantly affected their potential to exercise and enjoy property rights, which is considered one of the most effective means of empowerment and advancement, both from the context of their economic independence and self-determination. Proactively taking into account the aforesaid context through a systematic review of the existing literature and statutory norms, this paper aims to identify the byproducts of gender-based disparity, focusing on discriminatory property rights of Hindu women in Bangladesh. The paper strives to assert a firm stance against the violation of gender justice in Hindu women’s property rights. Also, with functional distributive fairness guaranteed in society as a whole, this endeavour will forge an emphatic voice for the inclusion of gender-neutral property rights.